A study on management of hypertension in patients with type 2 diabetes mellitus in tertiary care teaching rural hospital - Brahmbhatt, Shruti Vihang; Sattigeri, Bhagya M. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: This study was aimed to analyze the drug utilization pattern in the management of hypertension in diabetic patients. Methods: A prospective, observational and non interventional study was conducted in 100 diabetic hypertensive patients admitted in medicine wards at Dhiraj Hospital. Patients who signed informed consent form were only included in the study. All the data were recorded from patients’ case files and analyzed. Results: Of enrolled 100 patients, 69 (69%) were male and 31 (31%) were female and maximum number of the patients (42%) were found in the age group of 51-60 years. Out of 100 admitted patients, 75% patients were treated with single antihypertensive agent, 20% were treated with combination of two antihypertensive agents while only 5% were administered more than two antihypertensive agents. As a single antihypertensive agent, most commonly prescribed was ACE inhibitors (32%), Calcium Channel Blockers (23%), Angiotensin Receptor Blockers (12%) and β1 blockers (8%). Conclusions: There was poor awareness among the patients regarding control of hypertension, regular follow up, medication adherence etc. However, two third of diabetic patients had achieved blood pressure target control and ACE inhibitor remained first choice of drug for hypertension in diabetes in this study.